AUDIO RELAKSASI MUSIK LULLABY TERHADAP KUALITAS TIDUR PADA ANAK USIA PRASEKOLAH (4-6 TAHUN) : STUDI DI TK TUNAS HARAPAN DESA SIDOMULYO KABUPATEN TRENGGALEK - Nila Ayu; Linda Ishariani; Melani Kartika Sari (STIKES dan AKZI Karya Husada Kediri, 2022)
Preschoolers aged 4-6 years need approximately 11 hours of sleep a day as a need for rest and sleep. But not all preschool age children are able to meet these needs so that the quality of their sleep is also not met properly. Relaxation music as a means to help children meet their sleep needs, especially sleep quality. This study aims to determine the effect of lullaby music relaxation audio on the sleep quality of preschool children (4-6 years) in Tunas Harapan Kindergarten, Sidomulyo Pule village, Trenggalek district. The design used in this research is